Social access and dispersal of condiments in North-West Europe from the Roman to the medieval period - Livarda, Alexandra; Van der Veen, Marijke (Springer, 2008)
The introduction and dispersal histories of eight common condiments in North-West Europe are explored: celery, dill, coriander, black mustard, fennel, summer savory, caraway and parsley. The presence of these condiments in archaeobotanical reports from the study area was recorded, together with information on chronological phase, type of site, social status and mode of preservation. Analysis of the data suggests the presence of very distinct patterns of dispersal that highlight the socio-cultural significance of the foods in question.